Chromatic equivalence classes of certain generalized polygon trees, III - Omoomi, Behnaz; Peng, Yee-Hock (Elsevier, 2003)
Let P(G) denote the chromatic polynomial of a graph G. Two graphs G and H are chromatically equivalent, if P(G) = P(H). A set of graphs script S sign is called a chromatic equivalence class if for any graph H that is chromatically equivalent with a graph G in script S sign, then H∈script S sign. Peng et al. (Discrete Math. 172 (1997) 103-114), studied the chromatic equivalence classes of certain generalized polygon trees. In this paper, we continue that study and present a solution to Problem 2 in Koh and Teo (Discrete Math. 172 (1997) 59-78).